Islamic Moderatism in Curriculum Development Of Islamic Educational Institutions in Aceh - Junaidi; Afrinaldi; Febria Sri Artika; Mohammad Omar Al-Momani; Halad Hulwana (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2025)
Purpose – This study aims to analyze the moderation of Islam developed in the curriculum of Islamic educational institutions in Aceh, a special province with the implementation of Islamic law and a unique Dayah education system. Design/methods/approach – This study uses a phenomenological and sociological approach. In-depth interviews were conducted with leaders of Islamic boarding schools, madrasas, and schools, teachers, and students, accompanied by observation and documentation, which were analyzed using the Milles and Huberman model. Findings – The results of the study indicate that Islamic educational institutions in Aceh have provided their students with an understanding of religious moderation through the internalization of moderate religious values in the learning process. These Islamic moderate values are internalized through intraschool, extracurricular, and hidden curriculum programs by instilling attitudes that enable students to understand various deviations and differences in religious beliefs, act proportionally, non-discriminatorily, and respect ethnic and religious diversity. This moderate attitude can be found in social interactions between students, teachers, and people outside the school environment. Research implications/limitations – This study implies the importance of Islamic educational institutions in Aceh internalizing the values of Islamic moderation in the development of their curriculum to shape moderate attitudes in students. Originality/value – Many studies have been conducted on Islamic moderation in learning. However, studies on Islamic moderation in curriculum development in Islamic educational institutions in Dayah, Dayah Muhammadiyah, and Islamic schools in Aceh have not been explored much.